(untitled) (Journal of Social Sciences Review, 2025)
This study seeks to examine the influence of media in shaping public opinion and its implications for political decision-making since social media has become a fundamental aspect of global communication and information access. One possible consequence of social media is its capacity to galvanize public opinion, augmenting political engagement and influencing political decision-making. Social media functions as a medium for disseminating political information, enhancing political consciousness, and encouraging active engagement in the political process. This research employed a qualitative methodology to gather data from existing literature. The gathered data undergoes analysis in three phases: data reduction, data presentation, and conclusion formulation. The findings indicate that social media substantially influences public opinion and governmental decision-making in Iraq. This impact can be seen in the easy and quick access to political information, the creation of places where people can talk about politics, and the ease with which opinions and goals can be expressed.